ANALISIS FINANCIAL DISTRESS DENGAN MODEL ALTMAN Z-SCORE, ZMIJEWSKI, DAN SPRINGATE PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2023 - Hikmah, Nurul; Diana Riyana Harjayanti (Journal of Research and Publication Innovation, 2024)
Financial distress is the initial stage experienced by a company in the process leading to bankruptcy. If a company goes bankrupt, many parties will be adversely affected. Therefore, financial distress analysis is necessary to provide early warning for companies. The purpose of this study is to analyze the financial distress conditions of textile and garment sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2023 using the Original Altman Z-Score, Zmijewski, and Springate models. Additionally, this research aims to identify and analyze the most accurate model for predicting financial distress. The type of research used is quantitative descriptive research. The research population consists of all 25 textile and garment sub-sector companies listed on the IDX. The sample was selected using purposive sampling technique, resulting in six companies for the period 2018-2023. The data analysis models used are the Original Altman Z-Score, Zmijewski, and Springate models. This research was conducted by collecting secondary data from the Indonesia Stock Exchange website (www.idx.co.id) and the respective company websites. The results show that there are textile and garment sub-sector companies experiencing financial distress according to each model used. The Zmijewski model proves to be the most accurate in predicting financial distress, with the highest accuracy rate of 50%.